Experiences of building an ATM switch for the local area. - Black, Richard (Computer communication review.)
The Fairisle project was concerned with ATM in the local area. An earlier paper [9] described the preliminary work and plans for the project. Here we present the experiences we have had with the Fairisle network, describing how implementation has changed over the life of the project, the lessons learned, and some conclusions about the work so far.